2011
DOI: 10.1007/s10661-011-2195-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of digestion parameters for analysing the total sulphur of mine tailings by inductively coupled plasma optical emission spectrometry

Abstract: The oxidation of sulphidic mine tailings and consequent acid generation poses challenges for the environment. Accurate and precise analysis of sulphur content is necessary for impact assessment and management of mine tailings. Here, the authors aim at developing a rapid and easy digestion procedure, which may analyse and measure the total amount of sulphur in mine tailings by using inductively coupled plasma. For evaluating effects of several variables, the researchers used a univariate (analysis of variance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Prior to testing, tailings were air dried for 24-48 h and placed in an airtight sealed pack. The analysis of particle size distribution showed that the tailings contain mainly fine solids, with D 50 0.015 mm [22] and 97% of solids are finer than 74 m (passing #200 sieve).…”
Section: Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior to testing, tailings were air dried for 24-48 h and placed in an airtight sealed pack. The analysis of particle size distribution showed that the tailings contain mainly fine solids, with D 50 0.015 mm [22] and 97% of solids are finer than 74 m (passing #200 sieve).…”
Section: Samplesmentioning
confidence: 99%
“…Standard reference material RTS-2 (S = 18.95 wt.%) was used for calibration. Hot plate digestion followed by ICP-OES analysis of total sulphur was done according to procedure described by Alam et al [22]. In addition, the X-ray diffraction (XRD) data were obtained using a Rigaku-MiniFlex II, powder diffractometer (Japan), using CuK␣ ( for K␣ = 1.54059Å) over the desired 2Â range with a step width of 0.05 • .…”
Section: Apparatusmentioning
confidence: 99%
See 3 more Smart Citations